IMPLEMENTATION OF THE IBRAH MAUIDZAH METHOD IN LEARNING OF THE QURAN-HADITH AT MTS MUHAMADIYAH BANDUNG - Asep Abdul Aziz; Supiana Supiana; Muhibbin Syah; Hariman Siregar (Universitas Pendidikan Indonesia, 2022)
The moral condition of adolescents occupies a worrying position. Maximum efforts are needed to direct the morals of teenagers so that they can have noble character. One solution is through learning Islamic education, including through Quran-Hadith subjects. Quran-Hadith subjects are important subjects, because the Koran and Hadith are references for Muslims. In implementing the learning process, of course, each school has its own characteristics. This study aims to photograph the implementation of the Ibrah-Mauidzah method used in the Quran-Hadith learning process at MTs Muhamadiyah Bandung. This research method uses qualitative methods with data collection techniques using observation, interviews and documentation. The results of this study indicate that the implementation of Quran-Hadith learning using the Ibrah-Mauidzah method at Mts Muhamadiyah through classroom activities, habituation activities, and extracurricular activities guided by Quran-Hadith teachers in order to familiarize Islamic values in the school environment